Internet of things in the food industry : challenges and opportunities for the internet of food things - Rogala, Anna; Nestorowicz, Renata, 1974-; Jerzyk, Ewa (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"The food industry is experiencing a digital transformation across the entire supply chain, from farm to fork. This book offers comprehensive insights into the challenges and opportunities faced, specifically examining the application of the Internet of Things. The authors analyse the benefits and the related threats from the perspective of the participants of the entire supply chain, including consumers. Taking the reader on a journey, the book begins with an analysis of technology use in farming, production, logistics and retailing before delving into the use of digitalization in educating consumers on sustainable consumption practices. The multifaceted analysis of the IoF potential combines science and practice, enriching theoretical analysis with case studies. The book will be of interest to those researching and studying across supply chain management, logistics, innovation and technology management and consumption, with a particular interest in the food industry"--
Keywords: Food industry and trade -- Technological innovations; Internet of things; Business logistics; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Consumer Behavior